Pelaksanaan Perjanjian Pembiayaan Yang Didahului SKMHT (Surat Kuasa Membebankan Hak Tanggungan) Tanpa APHT (Akta Pemberian Hak Tanggungan) - Rindy Antika Putri; Devi Safitri (Jurnal Kajian Ilmiah, 2026)
In Indonesian banking practice, secured financing frequently involves the use of a Power of Attorney to Encumber Mortgage (Surat Kuasa Membebankan Hak Tanggungan/SKMHT) prior to the execution of the Deed of Granting Mortgage (Akta Pemberian Hak Tanggungan/APHT). The SKMHT functions as a temporary authorization for the Land Deed Official (PPAT) or Notary to execute the APHT; however, this instrument does not independently create a valid in rem security right. This article provides an in-depth analysis of the legal certainty and executorial power of financing agreements that have been disbursed but are supported solely by an SKMHT without the completion of a subsequent APHT. In addition, this study examines the responsibilities of banks and notaries/PPAT in safeguarding the legal certainty of collateral. The research employs a normative juridical approach, analyzing relevant regulations (the Mortgage Law and the Indonesian Civil Code) and reviewing Supreme Court decisions to assess how the norms are applied in practice. The findings indicate that an SKMHT without an APHT lacks executorial force (parate executie) because the mortgage right has not yet been established, thereby positioning the bank merely as a concurrent creditor. This study underscores the urgency of strict internal controls and effective coordination between banks and notaries/PPAT as essential strategies in managing the legal risks associated with secured financing